Promoting physical activity among youth and adolescents: "Active Break" project - Santarém, Daniel; Mendes, Jorge; Teixeira, Bruno; Ribeiro, Raquel; Fonseca, Sandra (VIREF Revista de Educación Física, 2024)
Problem: globally, physical inactivity is a major cause of mortality; a high percentage of the population does not satisfy the World Health Organization’s guidelines (WHO). The subject of Physical Education assumes an essential role since it provides a positive effect on the levels of physical activity of moderate-vigorous intensity in children and adolescents. Although the subject may only provide a few lessons per week, the school environment itself is considered the best environment to promote physical exercise. In order to decrease the prevalence of physical inactivity in the target population (predominantly adolescents), the "Active Break" programme emerged as an intervention aimed at increasing the levels of physical activity in a motivating and harmonious way. Objective: to describe the school intervention program called "Active Break". Results: due to administrative-logistical issues related to the school year planning, the implementation of this project took place in only one session, which limited the improvement at the level of practical intervention. However, the feedback we received from the students was positive and they showed willingness to repeat the experience, therefore this project can be a basis for its subsequent implementation in educational institutions. Conclusion: although the number of weekly sessions is small compared to the global recommendations provided by the WHO, the gradual increase in healthy habits can provide significant long-term improvements. The programme can be seen as a health promoter in a health promoting school. It is expected that this project will be useful to motivate the implementation of educational actions aimed at preventing or mitigating the negative effects of a sedentary lifestyle in young people.